Job Rotation: Strategi Inovatif untuk Mengasah Kepemimpinan Kepala Sekolah di SDN Cigugur Tengah Mandiri 2 - Sapitri, Riris; Purwanto, Nurtanio Agus (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
Abstract Principal leadership development is a key factor in improving the quality of education. One strategy that can be implemented is job rotation, which allows principals to gain diverse experiences. This study examines how the principal of SDN Cigugur Tengah Mandiri 2 developed his skills through additional duties as a training facilitator for active learning and school-based management in Cimahi City. This study used a descriptive qualitative approach with interview, observation and documentation techniques. Data were analyzed using the Miles and Huberman interactive model including data reduction, data presentation, and conclusion drawing. The findings show that job rotation provides diverse work experiences, which contribute to the development of principals' strategic, managerial and collaborative skills. In addition, these experiences encourage innovation in learning management and strengthen professional networks among principals. Job rotation proved to be an effective tool in improving principals' leadership capacity. Keywords: Job rotation, leadership development, facilitator, active learning, school-based management.